Level up : rise above the hidden forces holding your business back - Abrams, Stacey; Hodgson, Lara; Cabot, Heather (Portfolio/ Penguin, 2022)
"Stacey Abrams and Lara Hodgson draw on firsthand experience starting and scaling multiple companies over nearly two decades to crystallize their advice in Level Up, a how-to guide for small business owners. They share stories of building their own businesses, as well as actionable principles for founders looking to propel their ventures forward. They cover such topics as hiring, identifying a revenue strategy, recognizing when growth is a trap, and managing cash flow, and share the experiences of other successful founders including Jules Pieri of The Grommet, Alisa Clark of Glory Professional Services, and Sheila Jordan of Knowledge Architects"--